Polyphasic analysis of a middle ages coprolite microbiota, Belgium. - Sandra Appelt; Fabrice Armougom; Matthieu Le Bailly; Catherine Robert; Michel Drancourt (PLoS ONE)
Paleomicrobiological investigations of a 14(th)-century coprolite found inside a barrel in Namur, Belgium were done using microscopy, a culture-dependent approach and metagenomics. Results were confirmed by ad hoc PCR--sequencing. Investigations yielded evidence for flora from ancient environment preserved inside the coprolite, indicated by microscopic observation of amoebal cysts, plant fibers, seeds, pollens and mold remains. Seventeen different bacterial species were cultured from the coprolite, mixing organisms known to originate from the environment and organisms known to be gut inhabitants. Metagenomic analyses yielded 107,470 reads, of which known sequences (31.9%) comprised 98.98% bacterial, 0.52% eukaryotic, 0.44% archaeal and 0.06% viral assigned reads. Most abundant bacterial phyla were Proteobacteria, Gemmatimonadetes, Actinobacteria and Bacteroidetes. The 16 S rRNA gene dataset yielded 132,000 trimmed reads and 673 Operational Taxonomic Units. Most abundant bacterial phyla observed in the 16 S rRNA gene dataset belonged to Proteobacteria, Firmicutes, Actinobacteria and Chlamydia. The Namur coprolite yielded typical gut microbiota inhabitants, intestinal parasites Trichuris and Ascaris and systemic pathogens Bartonella and Bordetella. This study adds knowledge to gut microbiota in medieval times.